Protectin DX, a double lipoxygenase product from DHA, inhibits the production of both inflammatory cytokines and reactive oxygen species in human retinal pigment epithelium cells. Issue 8 (23rd February 2015) - Dai, Yining; Zhao, Chan; Liang, Xiaofang; Dai, Rongping; Dong, Fangtian
<x xml:space="preserve">Abstract</x> Oxidative stress and inflammation in retinal pigment epithelium (RPE) play important roles in the development of age‐related macular degeneration (AMD). Docosahexaenoic acid (22:6, n‐3, DHA) is highly concentrated in RPE and can be converted into the active oxygenate derivative protectin DX (PDX). The current study explored the effects of PDX on RPE cells under oxidative stress. Pretreatment with PDX significantly inhibited t‐BH‐induced reactive oxygen species (ROS) production and increased intracellular total antioxidant capability (T‐AOC) and superoxide dismutase (SOD) activity in RPE cells. Furthermore, PDX pretreatment greatly suppressed the t‐BH‐induced excessive secretion of tumor necrosis factor‐α (TNF‐α) and vascular endothelial growth factor‐A (VEGF‐A). Interestingly, peroxisome proliferator‐activated receptor‐γ coactivator‐1α (PGC‐1α), a key regulator of enzymes that detoxify ROS, was induced by PDX pretreatment, suggesting a possible mechanism that explains the antioxidant effects of PDX in RPE cells. Practical applications: DHA is highly concentrated in human RPE and photoreceptor cells. It remains controversial whether DHA can reduce the risk of progression to advanced AMD. The current study investigated the anti‐inflammatory and antioxidant effects of PDX on oxidative stress‐induced RPE cells. These results suggest the potential application of active oxygenated DHA derivatives in the prevention and treatment of AMD and other oxidative stress‐related retina diseases, such as diabetic retinopathy. <inline-graphic xlink:href="ark:/27927/pgj2cqnwzjj" content-type="ejlt201400423-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> DHA is highly concentrated in RPE and can be converted into the active oxygenate derivative protectin DX (PDX). Pretreatment with PDX significantly inhibited production of t‐BH‐induced reactive oxygen species (ROS) and increased capability of intracellular total antioxidant (T‐AOC) and activity of superoxide dismutase (SOD) in RPE cells. Furthermore, PDX pretreatment greatly suppressed t‐BH‐induced excessive secretion of tumor necrosis factor‐α (TNF‐α) and vascular endothelial growth factor‐A (VEGF‐A). Interestingly, peroxisome proliferator‐activated receptor‐γ coactivator‐1α (PGC‐1α), a key regulator of enzymes that detoxify ROS, was shown to be up‐regulated by PDX pretreatment, suggesting a possible mechanism underlying the antioxidant effects of PDX in RPE cells.